2010
DOI: 10.4061/2010/501541
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Antibodies to IDO/THO Pathway Metabolites in Alzheimer's Disease

Abstract: In Alzheimer's disease, indoleamine 2,3-dioxygenase and tryptophan hydroxylase are known to induce an overproduction of neurotoxic compounds, such as quinolinic acid and 3-hydroxykynurenine from the former, and 5-hydroxytryptophol and 5-methoxytryptophol from the latter. Other compounds, such as kynurenic acid, serotonin, and melatonin are produced via the same pathways. An improved ELISA method identified circulating antibodies directed against these compounds, linked to proteins, as previously described for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
(46 reference statements)
1
25
0
Order By: Relevance
“…With regard to the periphery, markedly increased levels of 3-OH-L-KYN [232] as well as elevated levels of circulating IgA directed against 3-OH-L-KYN [233] were found in serum samples of AD patients, though a study found only a trend for 3-OH-L-KYN to be increased in the plasma of AD patients [234]. This elevation in the periphery may at least in part underlie the elevated concentrations of 3-OH-L-…”
Section: -Hydroxy-l-kynurenine and 3-hydroxyanthranilic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the periphery, markedly increased levels of 3-OH-L-KYN [232] as well as elevated levels of circulating IgA directed against 3-OH-L-KYN [233] were found in serum samples of AD patients, though a study found only a trend for 3-OH-L-KYN to be increased in the plasma of AD patients [234]. This elevation in the periphery may at least in part underlie the elevated concentrations of 3-OH-L-…”
Section: -Hydroxy-l-kynurenine and 3-hydroxyanthranilic Acidmentioning
confidence: 99%
“…Furthermore, a gender difference was also demonstrated in this study, i.e., female AD patients had significantly higher CSF KYNA levels compared to the males, a difference not revealed in the control group. Interestingly, however, increased levels of circulating immunoglobulin A (IgA) against conjugated KYNA were detected in the serum of AD patients, adding to the spectrum of controversial findings in the field [233].…”
Section: Kynurenic Acidmentioning
confidence: 99%
“…However, reports on KYNA levels in AD patients are inconclusive. Decreased KYNA levels,13,21 but response of endogenous antibodies directed against KYNA (indicating overproduction of KYNA), have been shown in blood from AD patients 14. Further, elevated22 or unchanged16 KYNA concentrations in the brain of AD patients have been found, and an earlier study have described reduced CSF KYNA levels in AD patients compared to healthy individuals 15.…”
Section: Introductionmentioning
confidence: 97%
“…Another branch, primarily in resident and reactive microglia as well as in infiltrating macrophages, forms the excitotoxic metabolite quinolinic acid (QUIN). The latter is an N -methyl- d -aspartate (NMDA) receptor agonist, whereas KYNA blocks several receptors, including the glycine-site and the glutamate recognition-site of the NMDA receptor,13 the alpha7-nicotinic acetylcholine receptor, as well as the α-amino-3-hydroxi-5-metylisoxazol-4-propansyra (AMPA) receptor at higher concentrations 14. KYNA is also known to stimulate the G protein-coupled receptor 35 (GPR35).…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of 3-HK have been found in early stages of Huntington's disease (HD) patients (Schwarcz et al, 1984;Reynolds and Pearson, 1989;Pearson et al, 1995;Guidetti and Schwarcz, 2003), in Alzheimer's disease (AD) -in which 3-HK is assumed to be relevant for memory alterations (Savvateeva et al, 2000;Duleu et al, 2010) -and in the putamen of Parkinson's disease (PD) patients (Ogawa et al, 1992; reviewed by Colín-González et al, 2013). Also, transgenic mice models (R6/2 mice, YAC 128, and the chimeric HdhQ) have shown a substantial elevation of the 3-HK content (Guidetti et al, 2000;Guidetti et al, 2006;Sathyasaikumar et al, 2010).…”
Section: Introductionmentioning
confidence: 96%